Pengaruh Umur Listing, Audit Tenure, dan Investment Opportunity Set terhadap Audit Report Lag - Damayanti, Riska; Saputra, Mohamad Raihan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to empirically test and prove the effect of Listing Age, Audit Tenure, and Investment Opportunity Set on Audit Report Lag. This research is a quantitative study with an associative method. The population in this study consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2018-2022. The sample was selected using a purposive sampling technique, resulting in a total of 47 companies. The research analysis method used is panel data regression analysis. Based on the F-test statistical results, Listing Age, Audit Tenure, and Investment Opportunity Set simultaneously affect Audit Report Lag. Based on the t-test statistical results, Listing Age and Audit Tenure do not significantly affect Audit Report Lag when examined individually. However, the Investment Opportunity Set significantly affects Audit Report Lag based on the t-test statistical results.